Quality of the diet during the COVID-19 pandemic in 11 Latin-American countries - Samuel Durán-Agüero; Alfonsina Ortiz; Patricio Pérez-Armijo; María Fernanda Vinueza-Veloz; Israel Ríos-Castillo; Saby Camacho-Lopez; Brian M. Cavagnari; Edna J. Nava-González; Valeria Carpio-Arias; Karla Cordón-Arrivillaga; Saby Mauricio-Alza; Jhon Jairo Bejarano Roncancio; et al. (BMC, 2022)
Abstract Background and objectives The confinement by COVID-19 has affected the food chain and environments, which added to factors such as anxiety, frustration, fear and stress have modified the quality of the diet in the population around the world. The purpose of this study was to explore diet quality during the COVID-19 pandemic in 11 Latin American countries. Methodology Multicentric, cross-sectional study. An online survey was applied to residents of 11 Latin-American countries, during April and May 2020, when confinement was mandatory. Diet quality was evaluated using a validated questionnaire. Result 10,573 people participated in the study. The quality of the food by country shows that Colombia presented the best quality, while Chile and Paraguay presented the lowest. When comparing the overall results of diet quality by gender, schooling and age, women, people with more schooling and people under 30 years of age, presented better diet quality. The regression model showed that the variables associated with diet quality were: age (df = 3, F = 4. 57, p < 0.001), sex (df = 1, F = 131.01, p < 0.001), level of education (df = 1, F = 38.29, p < 0.001), perception of weight change (df = 2, F = 135.31, p < 0.001), basis services (df = 1, F = 8.63, p = 0.003), and quarantine (df = 1, F = 12.14, p = 0.001). Conclusion It is necessary for governments to intervene to reverse these indicators, considering that inadequate feeding favors the appearance of no communicable diseases, which favor a higher risk of infection and worse prognosis with COVID-19.